THE PECULIARITIES OF THE QUALITY OF LIFE OF PATIENTS, SUFFERED FROM ANEURYSMAL SUBARACHNOID HAEMORRHAGE - Duve, K. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The analysis of data from a number of scientific sources shows that even those patients, with favorable outcomes after suffering from aneurysmal subarachnoid hemorrhage (aSAH), may often experience a decline in quality of life (QoL), both at the physical and psychosocial levels. The influence of functional dependence on the patient’s quality of life remains controversial, because among the number of patients, who save the ability of self-care, there exists a part of those, who are not able to return to their previous lifestyle, kind of activity, they have difficulties in their relationships and emotional disorders. The aim of study was to assess the quality of life of patients in recovery and residual periods of aSAH. Material and methods. We examined 114 patients (64.91 % - males, 35.09 % - females). The patients’ quality of life was studied by using the questionnaire SF-36. The control group consisted of 20 healthy participants, matched by age and gender. Results. The significant decrease in QoL of patients was observed in all scales, with the exception of physical functioning, vital activity and social functioning. It should be noted, that "mental health" scale rates correlated with the level of anxiety (r = -0,55) and depression (r = -0,61). In the different age groups, the QoL indicators were almost identical, with the exception of "physical functioning" component, because older patients received a lower score for this scale (p<0.01). Patients with a moderate level of disability were observed with a decline in all QoL categories of the scale SF-36. Patients, who were totally independent, had also a significant decline in all QoL scale components, with the exception of physical functioning. Conclusions. We found the decrease in QoL of patients in recovery and residual periods of aSAH, which does not depend on one’s level of functional dependence. The influence of anxiety (r = -0,55) and depression (r = -0,61) on the subscale "mental health" was established.